Strategy for Handling the Crime of Serious Persecution in Archery Cases in the Community: Criminology and Criminal Law Perspectives - Gunawan; Yeni Widowaty (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research discusses in-depth strategies for handling crimes of severe abuse that occur in the context of archery cases among the community by adopting a holistic perspective from criminology and criminal law. The aim is to analyze and compare these two different points of view, as well as explore the possibility of collaboration between them, resulting in a more practical approach to dealing with this problem. The method used in this research is library research, where data collection is carried out by reviewing various literature, books and reports that are relevant to the topic being discussed. The findings obtained indicate that integration between a criminological approach which focuses on aspects of prevention and rehabilitation with firm law enforcement from a criminal law perspective is critical to creating a comprehensive solution. Therefore, this study recommends the development of collaborative programs involving various stakeholders, including government, social institutions, and communities, to develop treatment strategies that are more effective in preventing severe abuse in society as a whole.